Gastroenterology in the Metaverse: The dawn of a new era? - Zhang, Chi; Feng, Shuyan; He, Ruonan; Fang, Yi; Zhang, Shuo (Frontiers in Medicine, 2022)
2021 is known as the first year of the Metaverse, and around the world, internet giants are eager to devote themselves to it. In this review, we will introduce the concept, current development, and application of the Metaverse and the use of the current basic technologies in the medical field, such as virtual reality and telemedicine. We also probe into the new model of gastroenterology in the future era of the Metaverse.